Pisni viri o Blažu Berkeju - Dončec, Akoš (Edinost in dialog, 2024)
The article deals with presenting written sources about the Slovenian evangelical priest Blaž Berke and his handwritten hymnal in Prekmurian language in Hungarian and Slovenian (from the 18th to the 21st century). These sources provide some insight into Berke's life, although they do not give us enough information, only some basic but incomplete life data. Other sources or professional literature focus on the pastoral, preaching, and literary work of Blaž Berke, which he carried out in today's Prekmurje and Hungary. In these analyses, we can see his importance in the religious life of Protestant Hungarian Slovenes and the significance of his songbook in the literature of Prekmurje.
Keywords: Berke, Blaž; hymnal; luteranizem; lutheranism; pesmarica; Prekmurian language; Prekmurje; prekmurščina; protestantism; protestantizem